Lightweight and High-Payload Robotic Gripper Using Shape-Memory-Alloy Actuator and Self-Locking Mechanism - Toshihiro Nishimura; Keisuke Akasaka; Kosei Ueno; Yosuke Suzuki; Tokuo Tsuji; Tetsuyou Watanabe (IEEE Access)
This study proposes a novel lightweight robotic gripper with a high-payload capacity using shape-memory-alloy (SMA) actuators and a self-locking mechanism. The multi-joint fingers of the developed gripper are driven by flexible SMA actuators. This multi-link structure and the SMA actuator’s compliance property due to its flexibility provide self-adaptability, enabling the robotic gripper to grasp various shaped objects. To achieve the high-payload capacity while overcoming the limited actuation force inherent in SMA actuator systems, this study developed a new self-locking mechanism with a belt-shaped ratchet structure. The developed gripper is designed for vertical pick-and-place operations using an enveloping grasp strategy, where objects rest on the fingers secured by the self-locking mechanism. This self-locking mechanism also allows the developed gripper to hold objects without requiring a continuous power supply while transferring them. This integration of the SMA actuators and belt-shaped locking mechanism not only reduces power consumption but also simplifies the gripper’s structure for its lightweight design. These features–lightweight structure, high-payload capacity, self-adaptive grasping function, and low-power consumption–make the proposed gripper particularly suitable as an end-effector for drones. The paper presents a mechanical analysis of the proposed design, along with experimental validations. Payload tests were also conducted, demonstrating the proposed gripper achieved a payload capacity of 76.9 N (7.85 kg) while weighing only 265 g. Furthermore, grasping experiments with various objects confirmed the effectiveness and versatility of the gripper’s design.